Pengaruh sosialisasi teknik problem focus coping untuk mereduksi stres akademik pada mahasiswa psikologi - Santoso, Tito (Maliki Interdisciplinary Journal, 2024)
How an individual deals with stress that occurs will adjust to how he assesses an event. Events that are considered a challenge will be a motivation to improve one’s abilities, whereas if an event is considered a threat then as a result he will face problems or self-aggrandizement such as distress, depression, and other obstacles. The purpose of this research is to increase understanding of concepts, aspects, causal factors, how to reduce academic stress using problem focused coping. This study used a quantitative pre-experimental design approach through a one-group pre-test post-test design. Sampling was carried out purposively using the academic stress scale. From the test results it was found that 13 students (65%) focused coping abilities were in the low category, 5 (25%) respondents were in the medium category, and 2 people (10%) were in the high category. Meanwhile, after being given the socialization treatment, it was found that the total number of 20 research respondents showed that overall they were in the high category (100%). Based on the results of this study, it can be proven that the socialization of problem focused coping has an influence on reducing academic stress on students.